2017
DOI: 10.1007/s41101-017-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Confronting Realities for Sustainable Livelihood in Developing Countries: Case Study Mekelle University, Ethiopia

Abstract: Water is becoming a scarce resource in terms of quantity and quality. Water supply enhancement measures are being taken with less attention given to wastewater management, leading to increased discharge of untreated wastewaters. Wastewater is emerging as an affordable and reliable alternative water supply for urban agriculture, supporting thousands of farmers. Extensive use of untreated wastewater for irrigation will without a doubt lead to accumulation of heavy metals in soils and crops, resulting in overwhel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…Metals like copper and zinc are essential for enzymatic activity and many biological processes at low concentrations but may become toxic at higher concentrations (Bhatia, et al, 2015). According to USEPA, 2012 as cited in Amare et al, (2017), nickel, cadmium and lead have no known essential functions or role in the body of living organisms but may be toxic even at low concentrations causing a potential health risk through the food chain. Hence, as Amare et al, (2017) further reported, knowledge about these heavy metals' and their concentration in water for use is important, more so because they can become a health risk via consumption of contaminated vegetables, milk, fruit, and drinking water.…”
Section: Treated Wastewater Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Metals like copper and zinc are essential for enzymatic activity and many biological processes at low concentrations but may become toxic at higher concentrations (Bhatia, et al, 2015). According to USEPA, 2012 as cited in Amare et al, (2017), nickel, cadmium and lead have no known essential functions or role in the body of living organisms but may be toxic even at low concentrations causing a potential health risk through the food chain. Hence, as Amare et al, (2017) further reported, knowledge about these heavy metals' and their concentration in water for use is important, more so because they can become a health risk via consumption of contaminated vegetables, milk, fruit, and drinking water.…”
Section: Treated Wastewater Qualitymentioning
confidence: 99%
“…According to USEPA, 2012 as cited in Amare et al, (2017), nickel, cadmium and lead have no known essential functions or role in the body of living organisms but may be toxic even at low concentrations causing a potential health risk through the food chain. Hence, as Amare et al, (2017) further reported, knowledge about these heavy metals' and their concentration in water for use is important, more so because they can become a health risk via consumption of contaminated vegetables, milk, fruit, and drinking water. Fortunately or unfortunately, they are typically not removed from wastewater even after treatment, causing risk of heavy metal contamination of wastewater-irrigated soils and, subsequently, can end up in the food chain (Bhatia, et al, 2015).…”
Section: Treated Wastewater Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…(Rai 2012;Tantawy et al, 2015;Thirumdas et al 2018;Saha and Rahman 2018). Thus water security is amongst the top five global crises regarding development impacts (Amare et al 2017). In addition, water bodies' contamination by HMs through discharging industrial wastewater is a worldwide environmental issue that needs to be properly addressed.…”
Section: Introductionmentioning
confidence: 99%